Tradisi dan Inovasi: Menelisik Peran Dayah dalam Meningkatkan Daya Saing Mahasiswa di Era Globalisasi Pendidikan Agama - Ruslan, Ruslan (Al-Ikhtibar: Jurnal Ilmu Pendidikan, 2025)
The development of Islamic religious education faces increasingly complex challenges due to social change, technological advancement, and globalization. Dayah, as a traditional Islamic educational institution, holds a strategic role in preparing students to compete in an increasingly competitive educational environment. This study aims to examine the role of dayah in shaping students’ academic foundations, enhancing their competitiveness, and identifying the challenges and solutions encountered in equipping students for the religious education sector. The research employs a qualitative field study approach, utilizing in-depth interviews with dayah administrators, students, and community leaders. Thematic analysis was conducted to explore the role of dayah in knowledge formation, learning strategies, and responses to various obstacles. The findings reveal that dayah plays a crucial role in building students’ foundational knowledge through mastery of classical texts and traditional learning methods such as sorogan and halaqah. Strategies to improve competitiveness include integrating religious and general sciences into the curriculum, character development, and the use of information technology. Despite these efforts, challenges such as limited technological infrastructure, outdated curricula, and negative perceptions of traditional religious education persist. Solutions involve curriculum adaptation, improved technological access, soft skills training, and community support. Thus, dayah serves as an agent of change capable of producing graduates who are not only religiously grounded but also competitive in the global landscape of religious education.